Guaianolide sesquiterpenes and benzoate esters from the aerial parts of Siegesbeckia orientalis L. and their xanthine oxidase inhibitory activity. (October 2021) - Thuy Hang, Dan Thi; Trang, Do Thi; Dung, Duong Thi; Hai Yen, Duong Thi; Hoang, Nguyen Huy; Bang, Ngo Anh; Cuc, Nguyen Thi; Nhiem, Nguyen Xuan; Thanh Huong, Phan Thi; Tai, Bui Huu; Van Kiem, Phan
Abstract: Five undescribed (four guaianolide sesquiterpenes and a benzoate ester derivative) and seven known compounds were isolated from the aerial parts of S. orientalis L. Their chemical structures were determined by extensive analysis of HR-ESI-MS and NMR spectroscopic methods. Absolute configurations were elucidated by experimental and TD-DFT calculated ECD spectra. Twelve isolated compounds exhibited potential xanthine oxidase inhibitory activity with IC50 values ranging from 0.76 ± 0.17 μM to 31.80 ± 0.97 μM. Molecular docking studies predicted that the binding energies of all isolated compounds with xanthine oxidase were lower than that of the positive control allopurinol. Benzyl 2-hydroxy-6- O - β -D-glucopyranosylbenzoate and benzyl 2-methoxy-6- O - β -D-glucopyranosylbenzoate displayed not only the best docking score but also the highest in vitro xanthine oxidase inhibitory activity with IC50 values of 0.76 ± 0.17 μM and 0.98 ± 0.26 μM, respectively. Graphical abstract: Five undescribed (four guaianolide sesquiterpenes and a benzoate ester derivative) and seven known compounds were isolated from the aerial parts of Siegesbeckia orientalis L. Twelve isolated compounds exhibited xanthine oxidase inhibitory activity with IC50 values in the range 0.76–31.80 μM. Image 1 Highlights: Five undescribed compounds were isolated from Siegesbeckia orientalis. Their structures were established by spectroscopic methods. Isolated compounds exhibited potential xanthine oxidase inhibitory activity. Docking scores predicted better than that of allopurinol.